Arbitrarily positive initial energy blowup and blowup time for some fourth-order viscous wave equation. (July 2020) - Wang, Yu; Wu, Furong; Yang, Yanbing
Abstract: This paper is devoted to the finite time blowup phenomena for a class of fourth-order wave equation with viscous damping term. It is shown that the high initial energy finite time blowup associated with the upper bound of the blowup time is established by introducing a new auxiliary function and employing an adapted concavity method.